A Multidisciplinary Technique for Concurrent Panniculectomy–Living Donor Renal Transplantation. Issue 4 (April 2020) - Ngaage, Ledibabari M.; Messner, Franka; McGlone, Katie L.; Masters, Brian M.; Highstein, Mallory; Chopra, Karan; Phelan, Michael; Singh, Devinder; Scalea, Joseph; Niederhaus, Silke V.; Bromberg, Jonathan S.; Bartlett, Stephen T.; et al.
Abstract : Background: Recently, it has been shown that panniculectomy concurrent to living donor renal transplantation is a safe option for management of renal transplant recipients with a large focal pannus. This combined management requires precise coordination of teams. We describe the technique, timing, and sequence for combined renal transplantation and panniculectomy. Methods: We conducted a retrospective chart review of adult patients (≥18 years old) who underwent simultaneous living donor renal transplantation–panniculectomy from 2015 to 2019. A multi–team approach that included urology, transplant, and plastic surgery was used to perform the combined operations. Typically, the plastic surgery team initiates the operation by performing the panniculectomy. This is followed by kidney transplantation and graft anastomosis. The plastic surgery team then completes the operation with closure of the wound. Results: Twenty patients were identified. Most were male (12:8) with a mean age of 55 years and an average body mass index of 35 kg/m 2 . The mean total operative duration was 394 minutes. On average, 17% of operating time was devoted to panniculectomy. At 90 days follow-up, there was 100% graft survival and all patients had primary graft function. There was a 25% wound complications rate and a 15% reoperation rate. Conclusion: By performing panniculectomy first in the sequence, concurrent panniculectomy provides wide exposure and a large operative field for transplantation. Wound closure by plastic surgeons may mitigate the high complication rate commonly seen in obese patients with end-stage renal disease. Future studies are needed to evaluate the cost-benefit of the combined living donor renal transplantation–panniculectomy.